Online Repurchase Intention: Empirical Study on The Fashion Market Shopee - Alviona Allencia Gunawan; Irene Cahya Natalia; Priskadina Febriati; Vicky Viriyananda Hartono (Widya Manajemen, 2021)
The appearance of the Covid-19 virus makes people feel anxious, when they want to leave the house, when they want to do activities or shopping for necessities. With the fast development of the internet which is used by entrepreneurs to sell their goods through e-commerce. People are starting to use e-commerce to fulfill their needs, such as shopee, Tokopedia, Lazada and other e-commerce sites. Shopee is the object of this research, because Shopee has the largest number of active users in Southeast Asia. In this study we will use a combination of quantitative and qualitative methods. This study aims to determine the effect of trust, satisfaction, confirmation, perceived ease of use, perceived enjoyment , perceived usefulness and past internet shopping experience by the intention to repurchase on Shopee. Types of data used in this study using primary data and interviews. The population used in this study has the characteristics of making purchases or transactions for 1 year at shopee. The sample technique in this study used non-probability sampling. The analytical tool used is the Structural Equation Model (SEM) using AMOS 22.0 software. The results obtained from this study indicate that there are 11 supported hypotheses and 4 unsupported hypotheses